Manejo integrado del insecto barrenador (Diatraea saccharalis) en el cultivo de arroz (Oryza sativa) - Olvera Alvarado, Andrés Alfredo (2020)
Rice is one of the main products of the basic food basket in homes, as well as one of the main sources of employment for many Ecuadorians. Diatraea saccharalis is a pest that affects rice cultivation, notably reducing its yield, because its damage causes the loss of tillers. These insects attack in their larval stage, penetrating the stems of the plants, making galleries inside, causing it to reduce the growth of the floral primordium. When the larvae just emerge, they feed on the leaves and later enter the stem, feeding on it, causing a dead heart. The cultural measures that must be carried out are: the elimination of residues from past crops, weeds that serve as a source of host for the insect. This insect is one of the most common in rice cultivation, they are not found in large populations, but the small quantities that are found can affect a large part, since its incidence causes low yields in production.